1993
DOI: 10.1161/01.str.24.6.779
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of cerebral atherosclerosis in Hong Kong Chinese. Severity in intracranial and extracranial vessels.

Abstract: The clinical pattern of stroke and the angiographic distribution of cerebral atherosclerosis in Chinese are different from those in Caucasians. Pathological data from autopsy studies are lacking. The intracranial and extracranial arteries supplying the brains of 114 consecutive Chinese patients undergoing autopsy in a regional general hospital were examined by computer-assisted morphometric analysis under a microscope as well as by macroscopic grading for atherosclerotic narrowing. The severity was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
123
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(139 citation statements)
references
References 47 publications
13
123
3
Order By: Relevance
“…16,22 For example, the prevalence of intracranial compared with extracranial carotid disease varies among ethnic groups, with intracranial atherosclerosis more common in Asian and African populations and extracranial carotid and aortic arch atherosclerotic disease more common in white populations. 31,32 Therefore, a given pattern of atherosclerotic risk factors present in a population could result in different patterns of ischemic heart disease and stroke based on host factors alone.…”
Section: Other Factorsmentioning
confidence: 99%
“…16,22 For example, the prevalence of intracranial compared with extracranial carotid disease varies among ethnic groups, with intracranial atherosclerosis more common in Asian and African populations and extracranial carotid and aortic arch atherosclerotic disease more common in white populations. 31,32 Therefore, a given pattern of atherosclerotic risk factors present in a population could result in different patterns of ischemic heart disease and stroke based on host factors alone.…”
Section: Other Factorsmentioning
confidence: 99%
“…In particular, DM has been identified as a common vascular risk factor for ICS, even in different races 6, 14, 21, 25, 26. After multivariate logistic regression analysis, our study showed that DM was the most important determinant of IICS and an independent risk factor for both IICS and CEIS but not for IECS (Table 2, Figure 3).…”
Section: Discussionmentioning
confidence: 61%
“…Several risk factors, such as age, HTN, hyperlipidemia, metabolic syndrome, smoking, and DM, are regarded as major contributors to ICS 1, 6, 12, 13, 14. In particular, DM has been identified as a common vascular risk factor for ICS, even in different races 6, 14, 21, 25, 26.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with previous reports that showed diabetes mellitus to be preferentially associated with intracranial stenosis. An autopsybased study from Hong Kong reported an increased prevalence of intracranial stenosis in deceased patients with a past medical history of diabetes mellitus 23 . Bae et al showed that in patients with asymptomatic intracranial stenosis, diabetes mellitus was 1.86 times more likely to be present 9 .…”
Section: Discussionmentioning
confidence: 99%